THEORETICAL AND METHODOLOGICAL PROPOSALS FOR THE STUDY OF SMALL TOWNS - Sposito, Eliseu [UNESP] (Univ Vale Paraiba-univap, 2024)
Starting with stimulating questions, I outline a methodological proposal for the study of small towns, considering their importance both in the Brazilian urban network and in terms of the number of inhabitants they contain. To do this, I take into account the definition of a small town and the theoretical elements that can be identified in them, and then organise a set of methodological principles that can be followed in the research process, outlined in contradictory pairs, categories and concepts
Keywords: knowledge production; method; methodologies; small town